Large primary splenic cyst: A laparoscopic technique - Geraghty M; Khan I; Conlon K (Journal of Minimal Access Surgery, 2009)
Splenic cysts are rare lesions with around 800 cases reported in the world literature. Traditionally splenectomy was the treatment of choice. However, with the recognition of the important immunological function of the spleen, new techniques to preserve splenic function have been developed. This case emphasizes that in selected cases splenic preservation is appropriate.